Role of fine needle aspiration cytology in the diagnosis of thyroid lesions - Bhatta, S; Makaju, R; Mohammad, A (Journal of Pathology of Nepal, 2012)
Background: Fine needle aspiration cytology is regarded as a gold standard investigation in diagnosis of thyroid swellings. This study was carried out to evaluate the role of fine needle aspiration cytology as a diagnostic tool in investigation of thyroid swelling and to correlate the cytological findings with histopathology. Materials and Methods: A total of 90 patients with thyroid lesions submitted for fine needle aspiration cytology at Dhulikhel hospital Kathmandu Univeristy hospital over a four year period (May 2004 to May 2008) were studied. Results: Majority of cases were non neoplastic (77 cases, 85.55 %), whereas 13 cases (14.45 %) were neoplastic. Tissue examination was available for subsequent histocytological correlation in 20 cases (22.22 %). The accuracy of cytodiagnosis was 90 % with a sensitivity of 85.7 %, specificity of 92.3 %, false negative rate of 14.28% and false positive rate of 7.69%. Conclusion: Fine needle aspiration cytology of thyroid lesions provides a reliable diagnosis and is an excellent first line method for investigating the nature of lesion. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6018 JPN 2012; 2(3): 186-188